APPROACH TO ASTHMA AND MODALITIES OF MANAGEMENT - Nabeel Jaber Alharbi; Sultan Fahad Almaghrabi; Haytham Nabil Alhazmi; Atif Mohammed Hakami; Mohammad Zain Raddadi; Samirah Abdullah M Alameer; Hanan Mohammed Muadah Masrahi (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Asthma is a chronic respiratory condition characterized by inflammation in the airways, leading to recurring episodes of wheezing, breathlessness, chest tightness, and coughing. These symptoms often occur due to the airways' heightened sensitivity to various triggers, resulting in temporary narrowing and obstruction. Asthma can affect individuals of all ages, and its severity can vary from mild to severe. Aim: The literature review aims to overview the latest update on the approach to asthma and various management modalities. Methods: The present study is a comprehensive research of PUBMED from 2000 to 2023. Conclusion: Despite being prevalent in both children and adults, adults tend to have higher morbidity and mortality rates. Recent research suggests a possible link between sex hormones and asthma development. The disease's prevalence has increased globally, likely due to environmental factors. Asthma's pathophysiology involves complex interactions between immune cells and molecules, leading to airway inflammation, hyperresponsiveness, obstruction, and remodeling. Symptoms include wheezing, coughing, chest tightness, and breathlessness, which vary in severity and frequency. Asthma can manifest in different phenotypes, classified based on inflammatory cell profiles and clinical features. Diagnosis relies on clinical evaluation, lung function tests, and objective measurements. Treatment aims to control symptoms and prevent exacerbations using inhaled corticosteroids, long-acting β2-agonists, and combination inhalers.